The role of purple leaves extract (Graptophyllum Pictum (L.) Griff) on the number of fibroblasts and blood vessels in the socket after tooth extraction - Kurniawati, Atik; Kristanti, Yuli Dwi; Rahmat, Naila Azifatur; Rahayu, Yani Corvianindya; Cholid, Zainul; Sosiawan, Agung (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Tooth extraction is the process of removing teeth from the alveolus. It will leave a mark on the socket and surrounding soft tissue. One of the cells that plays an important role in the wound healing process after tooth extraction is fibroblasts. When an injury occurs, some blood vessels are damaged; therefore, new blood vessels need to form. Purple leaves extract could be an alternative treatment for wound healing after tooth extraction as it contains flavonoids, saponins, alkaloids, steroids, and tannins. Purpose: The study aimed to analyze the role of purple leaves extract on the increase in fibroblasts and blood vessels in the socket after tooth extraction in Wistar rats. Methods: The method used was a laboratory experiment with a post-test-only control group design. The samples used were 24 rats divided into two groups: the control group, which was given aquadest, and the treatment group, which was given 1.5 mL of purple leaves extract with 10% concentration by sondage. Tissue preparations were used to count fibroblasts, and blood vessels were counted and observed on the 3rd, 5th, and 7th days. Results: Statistical tests showed a significant difference in the number of fibroblasts and blood vessels between the control and treatment groups on days 3, 5, and 7. Conclusion: Purple leaves extract could increase the number of fibroblasts and blood vessels in the tooth socket after tooth extraction of Wistar rats.